Can child care policy encourage employment and fertility? Evidence from a structural model - Peter Haan; Katharina Wrohlich (Institute for the Study of Labor (IZA), 2009)
In this paper we develop a structural model of female employment and fertility which accounts for intertemporal feedback effects between the two outcomes. We identify the effect of financial incentives on the employment and fertility decision by exploiting variation in the tax and transfer system which differs by employment state and number of children. To this end we simulate in detail the effects of the tax and transfer system including child care costs. The model provides estimates of structural preferences of women which can be used to study the effect of various policy reforms. In particular, we show that increasing child care subsidies conditional on employment increases labor supply of all women as well as fertility of the childless and highly educated women.
urn:nbn:de:101:1-20091104979
Keywords: C23; C25; J22; J64; 330; Employment; fertility; financial incentives; Kinderbetreuung; Familienpolitik; Wirkungsanalyse; Frauenerwerbstätigkeit; Arbeitsangebot; Fruchtbarkeit; Deutschland